Deteksi Objek Menggunakan YOLO V3 Untuk Keamanan Pada Pergerakan Kursi Roda Elektrik - Wahyu Krisna Wijaya; I Komang Somawirata; Radimas Putra Muhammad Davi Labib (Nucleus Journal, 2022)
Image processing system is a system that has been developed to date. By using an image processing system, an image can be processed into the required information. In this study, an image processing system was created using the You Only Look Once (YOLO) algorithm which is a part of the Convolutional Neural Network (CNN) [1]. This system can be applied to electric wheelchairs, especially for detecting objects from the road surface they pass. The system that will be created is to detect objects in front of the wheelchair using image processing with the You Only Look Once (YOLO) algorithm method for the safe movement of electric wheelchairs. So when the wheelchair is running, it will simultaneously detect obstacles in front of it, both from the condition of the road surface and objects in front that will block the path of the electric wheelchair. Then, the detection results will be displayed on the monitor screen in front of the driver. As a result, detection can be used for braking control of the movement of electric wheelchairs to support security systems, but here the focus is more on object detection.